Keefektifan Perlakuan Panas Kering dan Iradiasi UV-C untuk Mematikan Cendawan Model Microcyclus ulei - Aprida Cristin; Meity Suradji Sinaga; Abdul Muin Adnan (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
This study was carried out to develop treatment methods and determine the effective dose of dry heat treatment and UV-C irradiation to kill the fungus models of Microcyclus ulei on soybean grains and soybean meals without damaging its nutritional content. The fungus models used in this study were Colletotrichum gloeosporioides, Botryodiplodia theobromae, Fusarium oxysporum f. sp. niveum, and Sclerotium rolfsii. The results showed that UV-C treatment up to 12 and 24 hours exposure time at15 and 30 cm from UV-C light was not effective to kill all fungus models in PDA. Dry heat treatment at 55 °C for 30 and 60 minutes was effective to kill cultures of C. gloeosporioides, B. theobromae, and S. rolfsii in PDA, except for F. oxysporum f. sp. niveum. Further experiments on soybean showed that dry heat treatment at 55 °C for 30 minutes was effective to kill conidia of C. gloeosporioides, B. theobromae, and F. oxysporum f. sp. niveum, without damaging its protein content. However, dry heat treatment at 60 °C for 60 minutes has been proved not effective to kill sclerotia of S. rolfsii. If M. ulei had the similar resistance as S. rolfsii, then it would need a higher temperature and time than used in this study to kill the fungusKey words: Botryodiplodia theobromae, Colletotrichum gloeosporioides, effective doses, Fusarium oxysporum f. sp. niveum, Sclerotium rolfsii, soybean meals